Biased Signaling of Protease-Activated Receptors - Zhao, Peishen; Metcalf, Matthew; Bunnett, Nigel W. (Frontiers in Endocrinology, 2014)
In addition to their role in protein degradation and digestion, proteases can also function as hormone-like signaling molecules that regulate vital patho-physiological processes, including inflammation, hemostasis, pain and repair mechanisms. Certain proteases can signal to cells by cleaving protease-activated receptors (PARs), a family of four G protein-coupled receptors. PARs are expressed by almost all cell types, control important physiological and disease-relevant processes, and are an emerging therapeutic target for major diseases. Most information about PAR activation and function derives from studies of a few proteases, for example thrombin in the case of PAR1, PAR3 and PAR4, and trypsin in the case of PAR2 and PAR4. These proteases cleave PARs at established sites with the extracellular N-terminal domains, and expose tethered ligands that stabilize conformations of the cleaved receptors that activate the canonical pathways of G protein- and/or β-arrestin-dependent signaling. However, a growing number of proteases have been identified that cleave PARs at divergent sites to activate distinct patterns of receptor signaling and trafficking. The capacity of these proteases to trigger distinct signaling pathways is referred to as biased signaling, and can lead to unique patho-physiological outcomes. Given that a different repertoire of proteases are activated in various patho-physiological conditions that may activate PARs by different mechanisms, signaling bias may account for the divergent actions of proteases and PARs. Moreover, therapies that target disease-relevant biased signaling pathways may be more effective and selective approaches for the treatment of protease- and PAR-driven diseases. Thus, rather than mediating the actions of a few proteases, PARs may integrate the biological actions of a wide spectrum of proteases in different patho-physiological conditions. Keywords: PARs, proteases, biased signaling, G proteins, β-arrestins, signal transduction